Judiciary of the 21st Century: How the literature suggests a new way to evaluate the Judiciary using the perception of citizens - Costa, Carlos A. L.; Laureano, Raul M. S.; Lavareda, Antonio; Alonso, Carla W. (Congresso Internacional de Gestão da Previdência Social - Congeps, 2023)
It is essential to implement a new way to evaluate the Judiciary considering the perception of citizens, especially in the XXI century, there is a pressing need to include society in the discussion of improvement of the public service. Apart from using information from specialists (Staats, 2005) such as lawyers, public servants and judges, the citizens can present a new perspective that will help to enhance the quality of the services of the Judiciary. The objective of this article is to present the state-of-the-art in the subject “Evaluation of the Judiciary” and how citizens’ perception could be a part of this process. Using Legitimacy (Dowling &Pfeffer, 1975), stakeholder (Freeman, 2010) and Social Power Theory (Russel, 1938), our study presents reasons why the citizen should be a part of the Evaluation of the Judiciary. The analysis was only qualitative and evaluated the literature behind the themes related to evaluation of the Judiciary. The analysis used 26 published articles, 14 books and 18 other documents including reports of stablished institutions. The results of the theoretical study showed that there is a lack of studies regarding citizen and Judiciary Evaluation (FGV, 2019), and therefore there will be a clear contribution if we stress the necessity of including citizen in a model of evaluation of the Judiciary. The implications of this research should affect the politicians, the Judiciary, the citizen and the academy. The politician, by giving new insights and inputs for them to develop public policy better adherent to what the citizen needs in terms of the Judiciary. It will also directly affect the Judiciary by improving their process. Managing the Judiciary would be more efficient and their processes could be optimized with the citizen's insights. A new type of evaluation, which includes citizen perception, should give more legitimacy to the Judiciary as a hole. For the citizen it would be beneficial to have more influence in the public sphere.